PENGARUH VARIASI DIAMETER PULI DAN KECEPATAN PUTAR BLOWER TERHADAP KAPASITAS HASIL DAN EFISIENSI MESIN PERONTOK PADI TIPE DRUM TERTUTUP - Nanda Gitara Rizkinada; Ikhwan Taufik; Raka Mahendra Sulistiyo (POLITALA PRESS, 2026)
The closed drum type rice thresher has constraints on the speed of the cylinder which is less than optimal, thus affecting threshing capacity and efficiency. This study aims to analyze the effect of pulley diameter variation (250, 300, 350 mm) and blower speed (500, 600, 700 rpm) on the performance of rice thresher using Ciherang rice variety. Airflow simulation was conducted with SolidWorks to determine the optimal direction and speed. The simulation results were validated with a small difference from direct measurement (0.128-0.475 m/s). Multiple linear regression analysis of 27 samples showed a simultaneous effect of pulley diameter and blower speed on yield capacity of 88.9% and threshing efficiency of 76.2%. The best combination was 300 mm pulley and 500 rpm blower with a capacity of 516,2 kg/hour and efficiency of 97,16%. In conclusion, variations in transmission and blower speed have a significant effect on the performance of the rice thresher.